The Ethics of Community: A Value-Based Exegesis of Surah Al-Hujurat - K M A Ahamed Zubair (Indonesian Journal of Research in Islamic Studies, 2026)
Background: Surah Al-Hujurat is widely recognised as a foundational chapter of Islamic social ethics, yet many interpretations emphasise legal rulings rather than its underlying moral architecture. Objective: This study aims to construct a value-based exegesis that identifies the core ethical principles embedded in the surah as a framework for community formation. Method: Employing thematic and deductive textual analysis, the study systematically examines the verses by organising them into three relational dimensions: human interaction with divine authority, intra-community relations among believers, and engagement with broader humanity. Results: The findings demonstrate that the surah articulates a coherent ethical system grounded in respectful communication, the verification of information, conflict mediation, the protection of dignity, and the safeguarding of privacy. It further establishes piety as the sole criterion of human worth, transcending lineage, ethnicity, and social status. Conclusion: Surah Al-Hujurat offers a comprehensive and enduring moral blueprint for cultivating just and cohesive societies. Contribution: This study advances a structured model of value-based exegesis that enriches contemporary Islamic ethical theory and communal discourse.